Integrated Groundwater Management 2016
DOI: 10.1007/978-3-319-23576-9_16
|View full text |Cite
|
Sign up to set email alerts
|

Managed Aquifer Recharge: An Overview of Issues and Options

Abstract: As covered in Chap. 2, many of the world's aquifers are rapidly being depleted. Nearly one quarter of the world's population -1.7 billion people -live in regions where more water is being consumed than nature can renew (Gleeson et al. 2012). Over-exploitation occurs when groundwater abstraction is too intensive, for example for irrigation or for direct industrial water-supply like extracting fossil fuels Foster et al. 2013). When groundwater is continuously over-pumped, year after year, the volume withdrawn fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 34 publications
0
33
0
1
Order By: Relevance
“…Currently, the operation by private water providers for peri-urban and rural water supply fits well to the hydrogeological conditions and should be promoted. Management strategies to prevent future water supply shortages and mitigate salinity impacts should consider the use of managed aquifer recharge (MAR) methods for its proven efficiency (Cassanova et al 2016;Dillon et al 2019). The constructed models can be used to assess the feasibility of MAR application in the Great Maputo area.…”
Section: Management Of Groundwater Abstractionmentioning
confidence: 99%
“…Currently, the operation by private water providers for peri-urban and rural water supply fits well to the hydrogeological conditions and should be promoted. Management strategies to prevent future water supply shortages and mitigate salinity impacts should consider the use of managed aquifer recharge (MAR) methods for its proven efficiency (Cassanova et al 2016;Dillon et al 2019). The constructed models can be used to assess the feasibility of MAR application in the Great Maputo area.…”
Section: Management Of Groundwater Abstractionmentioning
confidence: 99%
“…Globally, but especially in arid and semiarid regions, managed aquifer recharge (MAR) is an increasingly used water management tool. It involves infiltration or direct injection of water into suitable aquifers to improve and secure long-term water supplies (Casanova et al, 2016;Dillon and Arshad, 2016). In most applications of MAR, the infiltration or injection of various water types (e.g., surface water, purified wastewater, stormwater runoff) typically creates a geochemical disequilibrium that triggers a wide range of water-rock interactions (Descourvieres et al, 2010a;Fakhreddine et al, 2015;McNab Jr et al, 2009;Treumann et al, 2014;Vanderzalm et al, 2010;Wallis et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it behooves MAR operators to consider these before initiating MAR projects. Like Casanova et al [45] noted of France, and Megdal et al's [46] discussion of the USA state of Arizona, Ghana's laws/legislation, to some extent, are explicit on the requirements that need to be met in order for MAR to be accepted. When compared with policies and administrative agencies/organisations, it can be concluded that the relevant existing laws provide better and more comprehensive information for MAR activities in the country, and failure to comply with them may result in the rejection of MAR projects.…”
Section: Environmental Assessment Regulations 1999mentioning
confidence: 99%